Cultural Heritage as Civilizing Mission: From Decay to Recovery - Falser, Michael (Springer, 2015)
This book investigates the role of cultural heritage as a constitutive dimension of different civilizing missions from the colonial era to the present. It includes case studies of the Habsburg Empire and German colonialism in Africa, Asian case studies of (post)colonial India and the Dutch East Indies/Indonesia, China and French Indochina, and a special discussion on 20th-century Cambodia and the temples of Angkor.